Prospective trial of microneedle fractional radiofrequency in the hand rejuvenation treatment. (26th April 2022) - Wu, Xianglei; Zhu, Jiafang; Liu, Ying; Cen, Qingqing; Shang, Ying; Yu, Wenxin; Lin, Xiaoxi
Abstract: Aim: This study aimed to evaluate the safety and efficacy of a novel therapeutic strategy, a microneedle fractional radiofrequency system, for hand rejuvenation. Material and Method: Sixteen subjects were enrolled in a self‐controlled evaluator‐blind prospective trial. All subjects received three microneedle fractional radiofrequency treatments at 4 weeks intervals. Hand volume was evaluated through subjective (Hand Volume Rating Scale) and quantitative measurements. Patients were also assessed on the Global Aesthetic Improvement Scale using digital photographs. Patients were followed up at 1, 3, and 6 months after the last radiofrequency treatment. Results: Statistically significant improvements on the Global Aesthetic Improvement Scale and Hand Rating Volume Scale were noted ( p < 0.05). Compared with the control side, the treated hand showed a 44% improvement in dorsal skin surface roughness ( p < 0.05). Quantitative measurements of hand volume showed a trend toward increased volume for the treated hand, but the difference was not statistically significant. Conclusion: We conclude that microneedle fractional radiofrequency is a safe therapeutic option for hand rejuvenation.